Role of interfacial humidity in regulating the UHPC–NC interface strength: Insights from experimental observations and MD simulations - Liu, Shaoyan; Kai, Mingfeng; Yao, Yingkang; Liu, Jiahui; Hu, Lingling; A, Hubao (Construction & building materials, 2025)
Ultra-high-performance concrete (UHPC)–normal concrete (NC) composite elements exhibit significant potential in the context of advancing construction industrialization. The fresh-on-fresh (FF) casting method can significantly improve the interface bonding performance between UHPC and NC. The enhancement effect of the FF casting method is heavily influenced by the interfacial humidity, but the underlying mechanism behind is far from being fully understood. In this work, experimental observations and molecular dynamics simulations are combined to explore the impact of interfacial humidity on interface bonding and underlying mechanisms when forming UHPC-NC layers using the FF casting method. By varying the placement environment during casting delay (standard curing, indoor film-covered, and indoor conditions), three typical interfacial humidity conditions are achieved. We find that the bonding strength of UHPC-NC interface decreases significantly with the decaying interfacial humidity. Utilizing the combined BSE and NI analyses, we observe that with the reduction of interfacial humidity, both the interfacial porosity and microcrack density are significantly elevated, which compromises the interlaced growth of hydration products across the interface. Based on the experimental observations, we build a set of microscopic-scale models of containing UHPC-NC interface under varying humidity conditions, and the critical roles of the interlaced growth of hydration products on the UHPC–NC interface strength are further revealed. Our results and findings deepen the understanding of the effects of the interfacial humidity on the UHPC–NC interface strength, providing theoretical basis for the development of UHPC–NC composite elements with exceptional mechanical properties in construction applications. •The bonding strength of Fresh-on-fresh cast interface decreases with the reduction of humidity.•The staggered growth of hydration production was weakened with the decrease of humidity.•Reduced interface mechanical properties relates to weaker staggered growth at the nanoscale.